Morphometric data of tachypleus gigas and carcinoscorpius rotundicauda from Pahang Balok River, Malaysia - Ramli, Riwan; Kassim, Zaleha; Subli, Nurliyana (AIJR Publisher, 2023)
This study discovers new findings, prepares and compiles new information and database regarding horseshoe crab (HSC) especially morphometric of T. gigas and C. rotundicauda in Balok, Kuantan, Pahang. There are two stations during sampling for collecting the data. One station is at mangrove and another one station is at the beach. For each individual HSC, the sex, weight, and morphometric were taken. The process was repeated in approximately 2 hours during newly high tide. Findings indicate that male T. gigas is 31% smaller than the female in terms of size. In contrast, the male C. rotundicauda is 20% smaller than the female. Horseshoe crabs can range in size from 290 to 1200 grammes and 230 to 516 millimeters for female T. gigas, and from 180 to 420 grammes and 244 to 378 millimeters for male T. gigas. The size ranges for male and female C. rotundicauda are 100 to 260 grammes and 269 to 337 millimeters, respectively. The morphometric data are vital for monitoring and studying horseshoe crab growth and relations among various parts of their body. The compilation of morphometric data could also help to enhance the conservation of marine biological diversity activities. This study should be done rapidly to monitor the survivors and changes happening in the environment. Yet, year-round monitoring is important to establish the morphometric study of HSC.